Strategi Pengajaran Pendidikan Agama Islam yang Efektif di Madrasah Ibtidaiyah Ihya Ulumiddin Banjarmasin: Perspektif Guru - Khairullah Khairullah; Erwan Yusuf (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to explore and analyze effective Islamic Religious Education (IRE) teaching strategies at Madrasah Ibtidaiyah Ihya Ulumiddin Banjarmasin, focusing on the perspectives of teachers. The research employs a descriptive qualitative approach involving in-depth interviews with seven IRE teachers and direct classroom observations to obtain a comprehensive view. The collected data were analyzed using thematic analysis techniques. The findings reveal that effective teaching strategies include the application of active learning methods such as discussions and Q&A sessions, the use of varied teaching media, and contextual approaches that connect material with students' daily lives. Teachers also emphasize the importance of adapting methods according to the characteristics and individual needs of students. Additionally, continuous training and managerial support are deemed crucial for enhancing teaching effectiveness. The results of this study are expected to contribute to the development of better and more adaptive IRE teaching strategies in the Madrasah Ibtidaiyah environment.